Frontiers of research on Chinese management. Issue 1 (4th April 2016) - Foo, Check Teck
Abstract : Purpose: The purpose of this paper is to provide a brief yet insightful survey of papers in the first issue of Chinese Management Studies . In the process, the founding Editor focuses on the key concepts and how scholars may further extend and build on the research undertaken. Design/methodology/approach: The Editor provides a snapshot of the research undertaken in the papers selected for this issue. Instead of simply summarizing the work undertaken, the Editor, where it is highly appropriate, incorporates aspects of underlying Chinese culture. For instance, how the Confucian concept of the doctrine of mean – very broad as it is in scope – is supported in research reported here. Also, in contradiction to what authors may have argued on meaningfulness of work per se, to highlight an old Chinese adage: for example, 工字不出头 (gong-zhi-bu-chu-tuo). A literal translation into English will fail to render the true intent of the phrase. What it means is that the Chinese character for "work" implies a much deeper meaning: The horizontal line on top of the vertical limits the potential of future growth. Other concepts are visualized for ease of readers grasping the key concepts. Findings: The series of papers here highlight the significance of research into managerial behaviors (negatively, tax aggression and abuse of power for self-enrichment), meaningfulness of work, reading of timeless Chinese novels, innovation (ZTE) and the knowledge organization, changing and transforming China and of Russian-Chinese (Taiwan) strategic alliances. The insights gained through these intensive research efforts ought to be shared with scholars globally. Social implications: The research in this issue has wide practical relevance as in highlighting the critical importance of a range of topics: Jiang Hu organizing theory, managerial behaviors, innovation and knowledge, Russo-Chinese strategic alliances, fit in strategic management and China-in-transition. This paper ties these together for the reader. Originality/value: Through a review of these papers, the Editor provides insights for scholars on the possibilities for extending the frontiers of research on Chinese management. Where relevant the Editor highlights additionally, perspectives from deeply rooted Chinese beliefs, values and philosophy.